The Influence of Organizational Culture on Employee Discipline In The Regional Personnel Agency of West Java Province - Yumna Galumbira, Anata; Emir Atharrazka, Muhammad (Decision, 2024)
This study aims to determine the Influence of Organizational Culture on Employee Discipline at the West Java Provincial Civil Service Agency (BKD). Based on the results of the study, it is known that there are problems with employee work discipline, namely disobedience to time regulations and disobedience to behavioral regulations at work. The research method used by the researcher is descriptive with a quantitative approach. The number of respondents in this study was 30 people. Data collection techniques were carried out through observation, interviews and questionnaires. The data analysis techniques used consisted of validity tests, reliability tests and simple linear regression tests. Based on the results of the research and observations conducted by the researcher regarding the Influence of Organizational Culture (X) on Employee Discipline (Y) of 0.627 if expressed as a percentage becomes 62.7%. Based on these analyzes, the hypothesis that the author proposes is that there is a positive influence between the Organizational Culture variable and the Employee Discipline variable at the West Java Provincial Civil Service Agency (BKD) can be accepted and proven true. After conducting research by distributing questionnaires, observations and interviews, related to the Influence of Organizational Culture on Employee Discipline at the West Java Provincial BKD, the researcher has a suggestion, namely that BKD needs to implement an organizational culture that always prioritizes discipline, productivity and effectiveness